Legal Responsibility of Coal Mining Companies for Environmental Damage in Lappariaja District, Bone Regency - Muhammad Afian Hatta; Nurul Qamar; Syamsul Alam (Faculty of Law, Universitas Muslim Indonesia, 2025)
This paper aims to: (1) To determine the role of law in supervising coal mining activities in Lappariaja sub-district, Bone Regency; (2) To determine the legal responsibility of coal mining companies for environmental damage caused in Lappariaja sub-district, Bone Regency. This paper uses a descriptive empirical legal research method. This approach was chosen because it is able to provide a comprehensive picture of the phenomenon of anarchic behavior of funeral escorts on the highway, especially in the context of the application of criminal law and the factors causing it. The results of the paper show that the Legal Regulations in Supervising Coal Mining are contained in Government Regulation No. 55 of 2010 concerning the guidance and supervision of the implementation of the management and implementation of mineral and coal mining businesses. Article 13 states that: the minister supervises the implementation of mining business management carried out by the Provincial Government and Regency/City Government in accordance with their authority. The Minister, Governor/Regent/Mayor in accordance with their authority supervise the implementation of mining business activities carried out by holders of IUP, IPR or IUPK. The Legal Responsibility of Coal Mining Companies for Environmental Damage caused is: Criminal Legal Responsibility, Civil Legal Responsibility and Administrative Responsibility. Writing recommendations: (1) for the government, it is hoped that in issuing permits for mining businesses, they should conduct case studies regarding environmental impact analysis (AMDAL); (2) For mining companies, it is hoped that they will manage waste responsibly and carry out reforestation and greening in former mining areas.